Rancang Bangun Sistem Informasi Pendaftaran Siswa Baru Berbasis Web Pada Pondok Pesantren Nurul Qur’an Betung Abab Kabupaten Pali - Darmin Darmin; Khana Wijaya; Yuntari Purbasari (Jurnal Minfo Polgan, 2024)
The impact of the development of information technology in the field of education is to facilitate a particular educational institution or agency in carrying out the process of accepting new students by using a web-based information system. The presence of this web-based information system will make it easier for the new student admissions committee to manage and store various data accurately regarding information on prospective new students, and the time needed to process and store data is relatively short compared to the manual process.